Gestión administrativa y su relación con la contratación y fiscalización de obras de infraestructura para los centros infantiles del buen vivir (C.I.B.V) del cantón Quevedo, año 2015 - Mendoza Véliz, Darlin Stalin (2016)
The Child Development Centers of good living - CIBV city of Quevedo, are funded by the Ecuadorian State through the MIES, is decentralized care through the services and products of INFA, Implementing Entities (self-government) and civil society ; are located in the parishes of the canton distintitas, have a team like Integrated Child Development Coordinator; Promoting comprehensive child care; Promoters power, was performed in order to verify the administration and its relationship with the hiring and supervision of infrastructure work in children's centers of good living in the Canton Quevedo, 2015, to analyze the relationship of administrative management in projects social infrastructure prior to his hiring in CIBV, verify paperwork processes inferred in contracting work to improve children's centers, check that techniques used for the construction and supervision of infrastructure projects. To carry out the work as research methods employed; inductive, deductive and analytical, while types are; descriptive and explanatory techniques were constituted by interviews, surveys. After completing the study it was possible to analyze the processes of steps that inferred in contracting work to improve children's centers could be sure that there are no administrative procedure for the registration and contracting process work for CIBV, technical used for hiring and overseeing the infrastructure work for CIBV are not employed in the hiring and supervision of work as they are not selected by the administration, on the other hand the administration has no technical contingency mitigate risks in hiring and supervision of work.